Ship to shore : A dictionary of everyday words and phrases derived from the sea - Jeans, Peter D. (Camden, Me. : International Marine, 2004)
Preface; Acknowledgements; Introduction...
Includes bibliographical references.
Keywords: English language -- Etymology -- Dictionaries; Naval art and science -- Dictionaries; English language -- Terms and phrases; Sailors -- Language -- Dictionaries; Seafaring life -- Dictionaries; Figures of speech